PENGEMBANGAN MODEL SUPERVISI AKADEMIK TEKNIK MENTORING BAGI PEMBINAAN KOMPETENSI PEDAGOGIK GURU KELAS - Nehtry Merukh; Bambang Suteng Sulasmono (Kelola: Jurnal Manajemen Pendidikan, 2016)
This research aimed to describe (1) Implementation of principal supervision at Tunas Gloria Elementary School, Kupang; (2) Problems in the implementation of principal supervision at Tunas Gloria Elementary School, Kupang; and (3) Creating of the academic supervision models of pedagogic competence guidance mentoring technique for homeroom teacher. This research is R & D (Research and Development) by following steps of development according to Sugiono (2009). Questionnaires, interviews and documentation studies were used as data collection techniques. Delphie technique was used as model validation. Results of research showed that (1) Implementation of principal supervision hasnot been performed according to principles of supervision performance, (2) problems in the implementation of principal supervision i.e. a written planning has not been made; purposes of supervision has not been constructed according to the needs of teachers; guidance for supervision performance was still insufficient; time demand for principal; the performance of supervision was only adjusted to the supervision of supervisor; the comprehension from principalin performing of evaluation. The final result was in the form of academic supervision models of pedagogic competence guidance mentoring technique for homeroom teacher that consists of 4 stages–planning, performance, evaluation and follow-up.